Removal of phosphate from fresh water using bioirontech process - U Yasmeen (2009)
BioIronTech is a biological process of employing iron-reducing bacteria to reduce ferric iron (Fe3+) to ferrous iron (Fe2+) under strict anaerobic conditions. The reduced iron can then react with the phosphate (PO43-) to form insoluble ferrous phosphates. This chemical reaction can be applied to remove phosphates from freshwater.